2013
DOI: 10.1002/pssc.201300023
|View full text |Cite
|
Sign up to set email alerts
|

Progress in fluoride laser ceramics

Abstract: A variety of Er3+‐, Tm3+‐, and Yb3+‐activated CaF2‐, SrF2‐, (Ca, Sr)F2‐ and (Sr, Ba)F2‐based fluoride laser ceramics have been prepared by the hot‐forming technique. Lasing of the SrF2:Yb3+, (Ca, Sr)F2:Er3+, (Ca, Sr)F2:Tm3+, (Ba, Sr)F2:Tm3+ and (Ba, Sr)F2:Yb3+ specimens with diode pumping has been observed for the first time. Thermal conductivity data for the above fluorite‐type laser materials are also presented and discussed. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…For the given sample, the total mass loss (37%) turned out to be sufficiently close to the theo retical value (38%), which was calculated for an Al(OH) 3 …”
Section: Results and Discussion Thermal Behavior Of Yttrium And Alumisupporting
confidence: 75%
See 1 more Smart Citation
“…For the given sample, the total mass loss (37%) turned out to be sufficiently close to the theo retical value (38%), which was calculated for an Al(OH) 3 …”
Section: Results and Discussion Thermal Behavior Of Yttrium And Alumisupporting
confidence: 75%
“…In recent years, one of the most significant achieve ments was the creation of laser ceramics [1][2][3], including YAG based materials, the spectral lasing characteristics of which are not inferior to those of sin gle crystals, but exceed some of their parameters [1,[4][5][6][7]. Technological schemes underlying the obtainment of transparent ceramics involve several successive stages: powder material synthesis, compaction, and com pression (sintering and pressing).…”
Section: Introductionmentioning
confidence: 99%
“…Investigating the solubilities of sodium and potassium fluorides in strontium fluoride is of interest. Strontium fluoride is an important matrix for solid-state photonics, it is used in the form of melt grown single crystals [2][3][4][5], optical ceramics [6,7], and in nanotechnology processes [6][7][8][9][10][11][12][13][14][15]. In many synthetic processes, the ions of sodium and/or potassium are in the protocols [16].…”
Section: Introductionmentioning
confidence: 99%
“…In order to identify the region of solid solutions based on SrF 2 , in addition to the classic techniques of research, we used the technique of nanotechnology: previous investigations have shown that under low temperature syntheses, as a rule, non-equilibrium phases of variable composition are formed, with the width of the homogeneity region of solid solutions based on components often correspond to the limiting width of the high-temperature solid solutions, or even exceed it [1,6,10,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 A concurrent and historical approach consists of hot-forming Yb:CaF 2 single crystals in order to obtain transparent ceramics. [13][14][15] Anyway, the preparation of fluoride green bodies generally does not involve wet shaping of the nanopowder because of the reactivity of fluorides in water. In this paper, we report the fabrication of fluoride transparent ceramics using a completely wet route and a strainless shaping of the green body, followed by a simple pressureless sintering.…”
Section: Introductionmentioning
confidence: 99%